Nitrogen Application Alters Growth and Yield of BRRI dhan28: Nitrogen Effects on BRRI dhan28 Yield - Jahan, Md Sarwar (SAARC Journal of Agriculture, 2025)
Nitrogen is not only a major nutrient but the most limiting nutrient element for rice production. The present study was conducted to examine the effect of different doses of nitrogen on growth and yield of BRRI dhan28. The experiment was conducted in a Randomized Complete Block Design (RCBD) with four replications. The treatments include six doses of nitrogen, 0 - 175 kg N ha-1 with an interval of 35 kg N ha-1 as urea. Data on growth and yield contributing characters of rice were collected and analyzed statistically. The optimum dose for BRRI dhan28 was estimated 140 kg N ha-1. Results showed that plant height (cm), tillers m-2 and dry matter (kg ha-1) yield increased significantly with increasing levels of N. However, at 60 DAT, plant height (cm), tillers m-2 and dry matter (kg ha-1) production with 140 kg N ha-1 were statistically similar to that displayed by other nitrogen doses. The yield contributing parameters especially the panicle m-2 and test weight (g) were found superior with the treatment of 140 kg N ha-1. Application of 140 kg N ha-1showed AE and PFP for N as 14.5 kg kg-1 and 23.31, respectively. Application of N fertilizer @ 140 kg ha-1 increased grain yield by about 62% compared to N-control treatment in BRRI Dhan 28.